Analysis the tracking eye of one expert sailor in a virtual simulator - Manzanares Serrano, A.; Menayo Antúnez, R.; Segado Segado, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In a boat race, sailors are constantly receiving information about the environment thanks to the senses. The most determining sense in a sailor and other sports is his sight (Reina, Moreno & Sanz, 2007), since thanks to it, stimuli present in sailing environment are received, determining his response. The approach we have used aims to describing the visual conduct of an expert racer for the minute before the start signal. Methods The competitor in the current research was the first in Rankin of Optimist Class, in the Region of Murcia (Spain). Was used an automated system of measurement which integrates the following instruments: a) VSail-Trainer® sail simulator and b) Eye Tracking System®. Research variables were the number of fixations, the location of the fixations and the fixations time on each location made by the competitor. The event was made up by 2 starts of simulated race, with stable conditions of wind, competitor and sea. The simulated race reflected the same conditions as a real start. Results The total number of eye fixations performed in the first start were 94, while in the second one were 86. In the first start, the greatest number of fixations, were located in tack of the sail, the remaining of the sail, sea, and rivals, while in the second start, the most frequent locations were, tack of the sail, the remaining of the sail, sea, rivals , and buoys of start. It is worth mentioning that eye fixations carried out during the second start were distributed in a more homogeneous way than in the first start. In the same way, the average fixations time is higher in the second start than in the first one. Discussion The results show that, in the second start the sailor performed a lower number of eye fixations, together with an increment of average fixations time, regarding the first start. As it is upheld by many authors, a visual search strategy is more effective when the number of fixations carried out is lower, as well as a greater length of the latest (Ávila & Moreno, 2003; Williams, Davids & Williams, 1999). Improvement in visual search strategy on the part of the sailor can be a consequence of his learning, due to the short period between the first and the second start and the resulting error assimilation.